1975
DOI: 10.1001/archpedi.1975.02120430016006
|View full text |Cite
|
Sign up to set email alerts
|

The "Otitis-Prone" Condition

Abstract: We studied the incidence of exudative otitis media in 488 patients followed up from birth. Forty-nine percent (240) of the patients had their initial episode of otitis media in the first year of life and only 12% (56) in the second year of life. Thereafter, the incidence decreased steadily. Patients having six or more episodes of otitis media before age 6 were termed "otitis prone." Fi f t y\ x=req-\ seven such patients were observed and this condition was found to be significantly related to the onset of otit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
70
0
4

Year Published

1976
1976
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(78 citation statements)
references
References 9 publications
4
70
0
4
Order By: Relevance
“…Thus, although this survey could not outline cause and effect in an ideal fashion, the results strongly indicated that early age at first AOM episode was an important risk factor for rAOM and that early first AOM episode occurred frequently among children in Nuuk and Sisimiut compared with fmdings in other studies from the Western world (Howie et al 1975, Vinther et al 1979, Ingvarsson et al 1982, Harsten et al 1989, Kvaerner et al 1997b) but in accordance with reports from Alaska (Reed et al 1967, Kaplan et al 1973. Furthermore, familial and ethnical predisposition for AOM, rAOM, and/or COM seems to exist and may be ascribed to both genetical (intrinsic) and environmental (extrinsic) influence.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Thus, although this survey could not outline cause and effect in an ideal fashion, the results strongly indicated that early age at first AOM episode was an important risk factor for rAOM and that early first AOM episode occurred frequently among children in Nuuk and Sisimiut compared with fmdings in other studies from the Western world (Howie et al 1975, Vinther et al 1979, Ingvarsson et al 1982, Harsten et al 1989, Kvaerner et al 1997b) but in accordance with reports from Alaska (Reed et al 1967, Kaplan et al 1973. Furthermore, familial and ethnical predisposition for AOM, rAOM, and/or COM seems to exist and may be ascribed to both genetical (intrinsic) and environmental (extrinsic) influence.…”
Section: Discussionsupporting
confidence: 62%
“…It has been indicated that early and massive nasopharyngeal colonization with potentially pathogenic bacteria may p1ay a role in the pathogenesis of OM especially in high risk populations (Leach et al 1994, Homøe et al 1996. Risk factors in studies from other parts of the world include race, male gender, cleft palate, young age at first AOM, episode, siblings in the household with URTI, parental history of OM, attendance in large size daycare centers, exposure to passive smoking, lack of breast feeding, feeding position, atopy, prematurity, use of comforter, poor housing standard, and social poverty (i.e., poor living conditions) (Christensen 1956, Howie et al 1975, Strangert 1977, Ingvarsson et al 1982b, Saarinen 1982, Vinther et al 1982, Ståhiberg et al 1986, Fleming et al 1987, Kero and Piekkala 1987, Shapiro 1988, Harsten et al 1989, Teele et al 1989, Alho et al 1990, Froom and Culpepper 1991, Duncan et al 1993, Bastos 1994, Aniansson et al 1994, Ey et al 1995, Marx et al 1995, Sorri et al 1996, Uhari et al 1996, Kvaerner et al 1997aand b, Stenstrom and Ingvarsson 1997a, Daly et al 1999. However, results are conflicting for several of these risk factors, and most have only slightly been found to increase the risk for AOM.…”
Section: Aimsmentioning
confidence: 99%
“…Lower immunoglobulin levels in otitis-prone children suggest a generalized decreased antibody response in otitis-prone children. Based on the clinical observation that some children experience recurrent episodes of acute otitis media (AOM), the term "otitis-prone" was introduced by Howie (1). In general, the otitis-prone condition is defined as three or more episodes of AOM in 6 mo or four or more episodes in 12 mo; up to 5% of all children comply with this definition (2,3).…”
mentioning
confidence: 99%
“…Due to this reason, inspite of the fact that spontaneous resolution of OME may occur in some cases with time, it is better to do an early surgical intervention to prevent unwanted sequelae. 15 It would benefit the child if the OME were identified in the early stages itself. Development of OME hampers language learning in the early years of life.…”
Section: Discussionmentioning
confidence: 99%